Triangular flow of negative pions emitted in PbAu collisions at √sNN=17.3 GeV - Adamová, Dagmar; Bielčíková, Jana; Braun-Munzinger, Peter; Busch, Oliver; Damjanović, Sanja; Dietrich, Lars; Esumi, ShinIchi; Filimonov, Kirill; Glässel, Peter; Krobath, Gernot; Milošević, Jovan; Petráček, Vojtech; et al. (Nuclear physics. A, Nuclear and hadronic physics, 2017)
Differential triangular flow, v3(pT), of negative pions is measured at sNN=17.3 GeV around midrapidity by the CERES/NA45 experiment at CERN in central PbAu collisions in the range 0-30% with a mean centrality of 5.5%. This is the first measurement as a function of transverse momentum of the triangular flow at SPS energies. The pT range extends from about 0.05 GeV/c to more than 2 GeV/c. The triangular flow magnitude, corrected for the HBT effects, is smaller by a factor of about 2 than the one measured by the PHENIX experiment at RHIC and the ALICE experiment at the LHC. Within the analyzed range of central collisions no significant centrality dependence is observed. The data are found to be well described by a viscous hydrodynamic calculation combined with an UrQMD cascade model for the late stages.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Available online 8 August 2016
Gesehen am 22.10.2018